The influence of the relative age effect in the Czech youth ice hockey league - Agricola, A.; Bozdech, M.; Zhánel, J. (Montenegrin Journal of Sports Science and Medicine, 2020)
The issue of Relative Age Effect (RAE) focuses on the causes and consequences of the failure to respect development patterns of individuals in relation to their success, especially in sports. This study aims to determine whether the influence of the RAE can be proven in the Czech youth ice hockey league (U15) (n=744). A Chi-Square test (x2) has shown that the influence in the whole investigated group cannot be rejected (x2=25.34, p<0.01, w=0.11). The RAE can be rejected in the group of players (n=78) from the three best teams of the competition (x2=3.09, p=0.38, w=0.11); the influence of the RAE can also be rejected in players (n=75) from the three worst teams (x2=0.53, p=0.91, w=0.05). The assessment of RAE on playing positions has shown that the RAE can be rejected (x2=7.31, p=0.06, w=0.22) in the most productive forwards (n=50) as well as in the least productive forwards (n=50) (x2=0.48, p=0.92, w=0.06). The RAE is rejected in the group of the most productive defensemen (n=50) (x2=1.71, p=0.11, w=0.11), and in the group of the least productive defensemen (n=50) (x2=4.15, p=0.25, w=0.17). The RAE cannot be rejected (?2=8.88, p=0.03, w=0.35) in the group of best goaltenders (n=24); the RAE is rejected in the group of the worst goaltenders (n=24) (x2=1.5, p=0.68, w=0.14). Although the results have proven that the RAE cannot be rejected in the entire research group, there is no evidence of its influence (with the exception of the best goaltenders) in individual playing positions.